2018
DOI: 10.1001/jamapsychiatry.2018.2475
|View full text |Cite
|
Sign up to set email alerts
|

The Latent Structure of Negative Symptoms in Schizophrenia

Abstract: These findings suggest that the recent trend toward conceptualizing the latent structure of negative symptoms as 2 distinct dimensions does not adequately capture the complexity of the construct. The latent structure of negative symptoms is best conceptualized in relation to the 5 consensus domains. Implications for identifying pathophysiological mechanisms and targeted treatments are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 50 publications
7
134
0
Order By: Relevance
“…Although the items in Anhedonia, Avolition, and Asociality subscales loaded to the same factor in a previous factor analysis in BNSS 9,18,24,26,27 and CAINS, 13 recent studies revealed that five or more factor models fit better than two-factor models in BNSS and CAINS. 28,[33][34][35] This is in line with the following idea in the original NIMH report: "The five domains may have separate neurobiological substrates and may represent separate therapeutic targets." 5 Some of the neurobiological tasks exploring the biological basis specific to the each of the five domains have been adopted in clinical studies.…”
Section: Discussionsupporting
confidence: 74%
“…Although the items in Anhedonia, Avolition, and Asociality subscales loaded to the same factor in a previous factor analysis in BNSS 9,18,24,26,27 and CAINS, 13 recent studies revealed that five or more factor models fit better than two-factor models in BNSS and CAINS. 28,[33][34][35] This is in line with the following idea in the original NIMH report: "The five domains may have separate neurobiological substrates and may represent separate therapeutic targets." 5 Some of the neurobiological tasks exploring the biological basis specific to the each of the five domains have been adopted in clinical studies.…”
Section: Discussionsupporting
confidence: 74%
“…21 Two recent CFA studies suggest that the failure to support the 2-dimension model may be because this model does not capture the complexity of negative symptoms and there may be additional dimensions of relevance. 22,23 Strauss et al 22 used CFA to evaluate the latent structure of the SANS, 24 BNSS, 25 and CAINS. 12 Four CFA models were examined.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-factor and hierarchical models provided excellent fit, with the 5factor model outperforming the hierarchical model. In a follow-up study, 23 we evaluated the validity and cross-cultural invariance of the 5-factor model reported by Strauss et al 22 The 4 aforementioned models were evaluated across 5 cross-cultural samples, with a total n = 1678 (location/language): Italy/Italian, Spain/Spanish, China/Chinese, Switzerland/German, and United States/English. Results replicated the original study, 22 indicating that 1-and 2-factor models provided poor fit for the data, but 5-factor and hierarchical models provided excellent fit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations